Energy efficiency improvement of thermal hydrolysis and anaerobic digestion of Posidonia oceanica residues. (15th October 2019) - De Sanctis, M.; Chimienti, S.; Pastore, C.; Piergrossi, V.; Di Iaconi, C.
Graphical abstract: Highlights: Lignin represents about 34% of Posidonia oceanica biomass. Energy balance of thermal hydrolysis and anaerobic digestion is extremely negative. Acid addition in thermal hydrolysis significantly improves the process energy efficiency. Abstract: Posidonia oceanica is the most abundant aquatic plant of the Mediterranean Sea where it plays great ecological importance. The accumulation of residues along the shore, however, creates a littering hardship for the territory due to their bad rotting smell and introduces an obstacle to the enjoyment of the beaches and tourist swimming. Posidonia oceanica residues may be valorized producing bioenergy by anaerobic digestion. Due to its high lignin content, however, a pretreatment step is required for enhance energy recovery. In the present study the effects of acid addition in the thermal hydrolysis step were evaluated in terms of energy balance, biogas production and solids reduction. The results obtained have shown that when thermal pretreatment was enhanced by adding hydrochloric acid (0.4% w/w), an improvement in methane production of 575% was obtained compared to thermal pretreatment only with specific biogas production as high as 0.241 ± 0.065 Nm 3 per kgVS of wet Posidonia or 0.138 ± 0.056 Nm 3 CH4 /kgVS. This result was ascribed to the defibration of lignocellulosic components operated by acidic thermal pretreatment which allowed the removal of 74%, 70% and 24% of cellulose, hemicellulose and lignin, respectively, during anaerobic digestion. The energy analysis carried out for treatment plants with capacity of 10 and 50 m 3 /d has shown that acid addition in the thermal hydrolysis step allows the energy balance to turn from extremely negative (energy demand is 8 to 10 times greater than the one produced) to positive values, with process energy efficiencies ranging from 22 to 35% with regards to the size of the plant.